A Study on Medicine Utilization Pattern in Outpatient Departments of Tertiary Care Centre in Kathmandu - Thapa, R.; Singh, S (Nepal Medical College Journal, 2019)
The main objective of this study is to analyze the prescribing pattern of medicine in outpatient departments of tertiary care centre in Kathmandu using World Health Organization (WHO) drug use prescribing indicators. As per WHO consideration, 100 prescriptions were taken from each outpatient departments (OPD) of Nepal medical college including Orthopedics, Obstetrics and Gynecology, Surgery, Medicine, Ophthalmology, Otorhinolaryngology, Pediatrics, Dermatology and Psychiatry. Analysis of variance (ANOVA) was used to assess the statistical significance between means between all departments. Among a total of 900, 47.7% were male and 52.3% were female. Average medicine per prescription was 2.43±0.039. Number of Medicines by generic name 76 (3.4%), antibiotics 416 (19.0%), Injection 34 (1.5%), from Essential Medicine List (EML) 1,312 (60.1%), Fixed Dose Combination (FDC) 468 (21.4%) and the polypharmacy (≥4) was 129 (14.3%). The average cost was NPR 404.72±19.3 (3.69; 1=109.41NPR) and duration of treatment was 16.43±0.73 days. Patient’s age had positive correlation with number of medicines (p=0.002) and negative correlation with antibiotics (p=0.988). Cost of treatment had positive correlation with number of medicines (p=0.00), EML (p=0.00), duration of treatment (p=0.00) and antibiotics (p=0.33). Average medicines, from EML, and antibiotic use were high in Otorhinolaryngology with statistical significance of difference between mean. Prescription with FDC and intravenous were significantly high in Obstetrics and Gynecology. Cost and treatment duration were significantly high in Psychiatry. Tertiary healthcares need to develop and implement specific guidelines for prescriptions writing and also should develop a system to record them.